Expletive "Pro" in Persian Language - Mehrzad Mansoori (̒Ilm-i Zabān, 2016)
Observing Extended Projection Principle (EPP), a DP should be generated or moved to Spec of TP with or without Phonological form. As stated by Rizzy (1982), a pro drop language can have expletive or non-expletive pro. The study has indicated that expletive pro, hereafter “pro puč” (a Persian expression means empty), is more sophisticated than it seems in Persian linguistic words. The study has classified pro puč into five categories. The present corpus-based study has showed that expletive pro and its real pronoun cannot be used interchangeably in any of the contexts.  Having searched pro puč in a qualified corpus, at least one case has been found in which expletive pro has been substituted with its non-expletive counterpart. Consequently, it has been argued that both form and function should be considered in language study, particularly in syntax.